Developing a hollow fiber infection model system to determine the PK/PD of conjugated oligoelectrolytes against clinically relevant pathogens - Wang, Ruolan (Nanyang Technological University, 2023)
The ability of microbes to develop antimicrobial resistance gives rise to the emergence of drug resistant strains whose infections are difficult to treat. Therefore, there is a pressing need for the development of novel drugs. One of the key stages in the drug discovery pipeline is understanding the pharmacokinetic/pharmacodynamic (PK/PD) of the new drug. The conventional in vitro methods for evaluating drug efficacy are often static and hence may not truly reflect the in vivo conditions. Recently, hollow fiber bioreactors have emerged as a model system to mimic in vivo drug pharmacokinetics (PK) and pharmacodynamics (PD), without the need to access animal model experiments which requires specialized handling and are expensive to maintain. This is a useful technique that may accelerate the development of novel antimicrobial compounds such as the conjugated oligoelectrolytes (COEs). COEs are a class of synthetic water-soluble molecules containing a conjugated core and pendant ionic groups. COEs that are sufficiently shorter in molecular length as compared to the lipid bilayer inhibit microbial growth due to their membrane disrupting abilities. While COEs are emerging as potential low-cost antimicrobial agents, an understanding of the PK/PD of COEs is still required. Hence, this research would aim at developing the hollow fiber infection model (HFIM) system to determine the PK/PD of COEs against clinically relevant pathogens that are often difficult to infect in conventional mouse models due to the intrinsic host defense mechanisms.